2007
DOI: 10.1111/j.1462-2920.2007.01422.x
|View full text |Cite|
|
Sign up to set email alerts
|

Aerobic uranium (VI) bioprecipitation by metal‐resistant bacteria isolated from radionuclide‐ and metal‐contaminated subsurface soils

Abstract: In this study, the immobilization of toxic uranium [U(VI)] mediated by the intrinsic phosphatase activities of naturally occurring bacteria isolated from contaminated subsurface soils was examined. The phosphatase phenotypes of strains belonging to the genera, Arthrobacter, Bacillus and Rahnella, previously isolated from subsurface soils at the US Department of Energy's (DOE) Oak Ridge Field Research Center (ORFRC), were determined. The ORFRC represents a unique, extreme environment consisting of highly acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 76 publications
4
75
0
3
Order By: Relevance
“…Given that U precipitates formed in the presence of cells contained larger amounts of P i than did the abiotic control (Table 3), we hypothesized that P i production by phosphatases facilitates U biomineralization, which has been observed in other systems (17)(18)(19). Whole-cell phosphatase activity of C. crescentus grown in PYE medium with and without U was tested with three different organic phosphate substrates: glucose-6-phosphate, fructose-1,6-bisphosphate, and glycerol-2-phosphate (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that U precipitates formed in the presence of cells contained larger amounts of P i than did the abiotic control (Table 3), we hypothesized that P i production by phosphatases facilitates U biomineralization, which has been observed in other systems (17)(18)(19). Whole-cell phosphatase activity of C. crescentus grown in PYE medium with and without U was tested with three different organic phosphate substrates: glucose-6-phosphate, fructose-1,6-bisphosphate, and glycerol-2-phosphate (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…strain N14), Sphingomonas sp. BSAR-1, Arthrobacter, Rahnella, and Bacillus has been found to facilitate U(VI) precipitation through the formation of uranium phosphate complexes (17)(18)(19). Phosphatases from these organisms have been cloned and expressed in Escherichia coli and other organisms, and the resulting engineered strains have been reported to efficiently precipitate uranium (20)(21)(22).…”
mentioning
confidence: 99%
“…In particular, extracellular polysaccharides (EPS) secreted by many microorganisms contain side groups with negatively charged ligands such as hydroxyl, carboxyl, or phosphate, which attract cations like U(VI) and reduce their mobility (8,9). Additionally, phosphatase enzymes have been reported to mediate U(VI) precipitation through the release of inorganic phosphate from organophosphates (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The overexpression of the polyphosphate kinase (ppk) gene in Pseudomonas aeruginosa results in the significant accumulation of polyphosphates which degrade under carbon-starved conditions, and the phosphates released therefrom precipitate uranyl out of the solutions (24). Several environmental strains, such as Cellulomonas, Arthrobacter, Rahnella, and Bacillus, isolated from contaminated subsurface soils of the Department of Energy's Field Research Centre (ORFRC) were shown to immobilize uranium as a biogenic phosphate mineral resulting from polyphosphate metabolism or organophosphate hydrolase activity (25)(26)(27).…”
mentioning
confidence: 99%
“…Previous studies on uranium bioremediation/biomineralization have focused on the bacterial reduction of U(VI) to uraninite or monomeric U(IV) under anoxic conditions or on enzymatic bioprecipitation in the presence of exogenous organic phosphate substrate under oxic conditions (15,25,(27)(28)(29) and anoxic conditions (30) below a circumneutral pH. However, much of the uranyl contamination found in groundwater/ aquatic systems exists above a circumneutral pH where uranyl mobility is predominantly controlled by carbonates through the formation of highly soluble and stable uranyl carbonate complexes (31).…”
mentioning
confidence: 99%